Christelike gesindheid en politieke protes - Vorster, J. M. (HTS teologiese studies, 2005)
Christian attitude and political protestIn Christian ethics the issue of protest has always been a widely discussed theme. Notwithstanding, the development of constitutional democracies all over the world, the topic has become even more prominent especially as it relates to the following issues: the position of minority groups in majority governments and the freedom of individuals to maintain a certain value system in various spheres of authority. This article discusses the nature of a Christian perspective on political protest and the role such Christian attitude can play. In this regard special reference is made to the strategies of armed resistance, civil disobedience and external pressure. The implementation of the classic idea of “uis ad bellum” is questioned on grounds of the current existence of weapons of mass destruction. Norms are formulated for the responsible use of civil disobedience and external pressure to promote freedom of choice and expression in a peaceful and constructive way.